Structure and regulation of the rat 1,25-dihydroxyvitamin D3 receptor. - Burmester, J K (1988)
Complementary DNA clones encoding the entire rat 1,25-dihydroxyvitamin D3 receptor were isolated, and the total 423-amino acid sequence was deduced. The amino acid sequence of the rat receptor is similar but not identical to the reported human receptor sequence. The cysteine-rich DNA-binding domain is completely conserved and the steroid-binding domain is greater than 93% conserved between rat and human. The cDNA was used as a probe in blot analysis of polyadenylylated RNA to show that the 1,25-dihydroxyvitamin D3 receptor mRNA is a single 4.4-kilobase mRNA that is expressed in intestine and kidney, slightly expressed in heart, and not detectable in liver and spleen. The receptor mRNA concentration is markedly increased during development of the rat intestine between day 14 and day 21, in accord with previous results obtained by measurement of receptor concentration by ligand binding or immunoblotting.